PARTISIPASI PETANI DALAM KEGIATAN KELOMPOK TANI (STUDI PADA KELOMPOK TANI TAMBAK IKAN AIR TAWAR “MITRA TANI” DESA PETIR, KECAMATAN DRAMAGA, KABUPATEN BOGOR) - Yuliarso, M. Zulkarnain (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
The objective of the study was to estimated levels of farmer’s participation in farmer’s group activity and identify internal factors that related to participation. This research was conducted in June 2004 at petir’s village of Dramaga Subdistric, Bogor. Data from 30 samples were selected using sample random sampling. Rank spearman analysis was used to identify factors influencing farmer’s participation. The study concluded that several internal factors namely formal education, motivation and perception have significantly related to levels of participation.